Multipliers of uniform topological algebras - El Azhari, Mohammed (Annales Mathematicae Silesianae, 2017)
Let E be a complete uniform topological algebra with Arens-Michael normed factors (Eα)α∈Λ. Then M(E)≅lim←M(Eα) within an algebra isomorphism ϕ. If each factor Eα is complete, then every multiplier of E is continuous and ϕ is a topological algebra isomorphism where M(E) is endowed with its seminorm topology.